Assessing the bond strength of short fiber composites to dentin using various air abrasion particles - Başol, Ece Ucar; Cekic, Isil Nagas; Garoushi, Sufyan; Nagas, Emre; Vallittu; Pekka, Kalevi; Lassila; Lippo Veli Juhana (Japan, 2025)
Purpose: This study investigated the bond strength between short fiber-reinforced resin composite (SFC) and dentin following air abrasion with various types of abrasive particles.
Methods: A total of 120 human molars were prepared for a shear bond strength (SBS) test of the resin composite. The teeth were divided into 12 groups (n = 10/group) based on the air abrasion particle used. Half of the groups underwent phosphoric acid etching (10 s) prior to air abrasion, while the other half received no pretreatment. Air abrasion was performed using five types of particles, after which a two-part adhesive (G2 Bond) and SFC were applied on the treated surfaces. The SBS test was performed using a universal testing machine at a crosshead speed of 1.0 mm/min until failure. Two additional specimens from each group were prepared to evaluate the air abraded surface using scanning electron microscopy after being stored in simulated body fluid (SBF) for two weeks. Statistical analysis was performed using two-way analysis of variance and the Tukey test (α = 0.05).
Results: The highest SBS values were observed in the control group (18.9 MPa), which did not undergo air abrasion. The use of different air abrasion particles affected the SBS of SFC to dentin (P < 0.05), as air abrasion with jet sand in the absence of pre-etching differed significantly from the other Cojet group (P < 0.05).
Conclusions: Air abrasion with various particles did not improve the bond strength between the SFC and dentin.